KONSTRUKSI MEDIA DAN ISU NEGARA ISLAM INDONESIA Analisis Framing Pemberitaan Koran Tempo tentang Isu Negara Islam Indonesia - Karman, Karman (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
Abstract The existence of NII (Negara Islam Indonesia) is an issue drawing a public attention since its declaration till present time. On April 2011, issue of NII came to fore and drew attention of mass media, including Koran Tempo. This research dealt with news of that daily regarding NII. Paradigm of this research is constructivism. Method of analysis is framing with model Robert M. Entmant. The results shows that there are themes emphasized by Tempo, id est: NII Recruitment Method; Target of area and Target of NII prospective member; NII Victims; Campus alertness due to NII existence; Relationship NII member and book-bomb case; Coersive & Anticipative action of government against NII. Resource persons quoted are from various circle, but their voice is same -the danger of NII socially, ideologically, and NII must be wiped out. From element of Define Problem, Tempo identified that the problem is NII as the organization which swindle peoples on behalf of faith, and its will to establish islamic state in Indonesia classified as subversive action. In element of Diagnose Causes, the problem of NII is caused by slugishness in taking an action, and inertia or powerlessness in uncovering NII network. Moral Judgement harnessed is that NII is a danger, its penetrated into campuses and bureaucracy, and brought about panic. In element of Treatment Recommendation, Tempo proposes that activities of NII be uncovered completely.